A novel support of nano titania modified graphitized nanodiamond for Pt electrocatalyst in direct methanol fuel cell. (13th April 2015) - Zhao, Yuling; Wang, Yanhui; Zang, Jianbing; Lu, Jing; Xu, Xipeng
Abstract Graphitized nanodiamond (GND) was prepared by annealing ND in a vacuum at temperature of 1300 °C for 2 h, followed by the synthesis of TiO2 modified GND (TiO2/GND) using a microwave hydrolysis method. TiO2/GND supported Pt (Pt/TiO2/GND) electrocatalysts were synthesized by a microwave-assisted polyol process and characterized. Pt nanoparticles (NPs) supported on Vulcan XC-72 carbon (Pt/C) and TiO2/C (Pt/TiO2/C) catalysts were obtained according to the same method for comparison. The TiO2/GND support showed much more excellent stability than carbon black and TiO2/C in acid solution, and Pt/TiO2/GND and Pt/TiO2/C catalysts showed enhanced electrocatalytic activity for methanol oxidation and oxygen reduction due to the synergistic effect of Pt and support. It is worth mentioned that the Pt/TiO2/GND demonstrated a better durability than the other two catalysts due to the higher stability of TiO2/GND support and the anchoring effect of the TiO2 layer to Pt NPs.